Re-Configurations : Contextualising Transformation Processes and Lasting Crises in the Middle East and North Africa - Ouaissa, Rachid; Pannewick, Friederike; Strohmaier, Alena (2021)
This edited volume is an open access title and assembles both the historical consciousness and transformation of the MENA region in various disciplinary and topical facets. At the same time, it aims to go beyond the MENA region, contributing to critical debates on area studies while pointing out transregional and cultural references in a broad and comparative manner.